STRATEGI PEMASARAN EVENT MAKEPUNG, JEMBRANA - Ni Ketut Ratna Dewi; I Made Sendra; Yohanes Kristianto (Jurnal IPTA)
This study aims to determine the internal and external factors that influence the Makepung Regent Cup Event as a cultural tourism attraction to obtain the right marketing strategy. This research uses the concept of the 4P marketing mix (Product, Price, Place, Promotion). The method used in this research is descriptive qualitative with a SWOT approach and described using a SWOT matrix. The data collection techniques used in this research are literature study, interviews, observation and documentation. The informant determination technique used is purposive sampling.The results of this study are as follows; 4P marketing mix, the products offered are cultural tourism, there are no special rates for tourists, the location of the circuit is classified as strategic, promotional efforts are carried out by advertising, direct promotion and sales promotion. The results of the SWOT analysis created a marketing strategy, namely: (1) SO strategy: Optimizing promotion through print media and utilizing social media by creating interesting content, (2) ST strategy: Maintaining the concept and uniqueness that is owned and the second strategy is maintaining local wisdom and community empowerment, (3) WO Strategy: Holding a special exhibition for the Makepung Event by modifying the beating tools used and by optimizing the quality of human resources in managing tourism opportunities, (4) WT strategy: Optimizing collaboration with stakeholders, and the second strategy is to improve supporting facilities in the circuit area.